2021
DOI: 10.1186/s13287-021-02196-x
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic mesenchymal stem cells to promote/suppress cancer: two sides of the same coin

Abstract: Cancer is a leading cause of death in both developed and developing countries, and because of population growth and aging, it is a growing medical burden worldwide. With robust development in medicine, the use of stem cells has opened new treatment modalities in cancer therapy. In adult stem cells, mesenchymal stem cells (MSCs) are showing rising promise in cancer treatment due to their unique properties. Among different sources of MSCs, human amniotic fluid/membrane is an attractive and suitable reservoir. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 136 publications
0
33
0
Order By: Relevance
“…Although the tumorigenic potential of MSCs has yet to be demonstrated in the context of clinical trials (22,23), it has been reported that MSCs with tumor tropism can promote tumor progression or, conversely, suppress tumor growth (4,5,7). In this study, we observed that ASCs overexpressing TRAIL induced apoptosis of H460 cells and efficiently controlled tumor growth, even in a xenograft model.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although the tumorigenic potential of MSCs has yet to be demonstrated in the context of clinical trials (22,23), it has been reported that MSCs with tumor tropism can promote tumor progression or, conversely, suppress tumor growth (4,5,7). In this study, we observed that ASCs overexpressing TRAIL induced apoptosis of H460 cells and efficiently controlled tumor growth, even in a xenograft model.…”
Section: Discussionmentioning
confidence: 61%
“…Numerous mediators secreted by MSCs are pro-tumorigenic: Immunosuppressive agents, angiogenic agents, mediators of the transition of MSCs into cancerassociated fibroblasts, epithelial-mesenchymal transitionpromoting agents, and tumor metastasis-promoting agents (5,6). In contrast, MSCs have also been reported to prevent tumor growth through anti-angiogenesis, cell-cycle arrest and apoptosis, down-regulation of survival signaling, and immune cell infiltration (7,8).Despite the anti-tumorigenic potential of MSCs, MSC-based tumor therapy is still limited due to the insufficient secretion of effector molecules and discrepancies between their in vitro and in vivo efficacy (8). To overcome these limitations, genetic modifications of MSCs have been proposed (9-11).…”
mentioning
confidence: 99%
“…Amniotic fluid-derived stem cells are considered as a new and potential experimental approach toward improving various conditions, such as autoimmune diseases (Yang et al, 2021), ischemic heart disease (Fang et al, 2021), and Alzheimer's disease (Gatti et al, 2020). They are also suggested to help to suppress cancer (Jafari et al, 2021) or even improve spermatogenesis (Mobarak et al, 2021). However, the main interest goes to treating congenital anomalies such as spina bifida, congenital diaphragmatic hernia, and congenital heart disease (Di Bernardo et al, 2014;Kunisaki, 2018;Abe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells migrate to the sites of inflammation, enhance malignant proliferation, and contribute to the expansion of the fibrovascular network and tumor progression ( Spaeth et al, 2009 ; Jafari et al, 2021 ). It is also known that MSCs protect cancer cells through TGF-beta dependent regulatory T cell mediated immune suppression ( Patel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%